Ranking of sustainability criteria for industrial symbiosis applications based on ANP - Alakaş, Hacı Mehmet; Gür, Şeyda; Özcan, Evrencan; Eren, Tamer (Journal of Environmental Engineering and Landscape Management, 2020)
Enterprises have started to establish partnerships both to use their internal resources efficiently and to increase their environmental performance. Partnerships and interoperability of enterprises with different processes enable them to benefit more from their benefits. Moving towards the local and regional economy, these partnerships that increase environmental and own resources have created industrial symbiosis practices. Industrial ecology fields are established in these applications. Both environmental and economic gains can be achieved through the efficient use of resources by enterprises and the minimization of wastes. For the sustainability of these partnerships to be established by enterprises, they need to analyze the measures they take internally. In this study, the concept of industrial symbiosis and the criteria that are effective for the sustainability of these industrial symbiosis are evaluated. Analytical network process method is used.  Thus, the industrial symbiosis infrastructures to be established by enterprises have been enabled to move strategically.